Towards REDD+ implementation: Deforestation and forest degradation drivers, REDD+ financing, and readiness activities in participant countries - Andoh, Jewel; Oduro, Kwame Antwi; Park, Joowon; Lee, Yohan (Frontiers in Forests and Global Change, 2022)
This study provides an assessment of dominant drivers of deforestation and forest degradation across 29 REDD+ participant countries and total funds disbursed from the Forest Carbon Partnership Facility (FCPF) to 15 participant countries since they signed their respective Readiness Preparation Proposals (R-PPs), as well as what they spent the grants on. This study aims to provide information for policymakers and donors on the need to invest in REDD+, as well as the need for participant countries to channel funds to key activities for effectively and efficiently implementing REDD+. The assessment is based on participant countries’ R-PPs and FCPF readiness fund progress reports, using a content analysis approach. The expansion of agriculture, which includes both commercial and subsistence agriculture, was the predominant driver of deforestation, while logging, such as industrial and small-scale exploitation, was the main driver of forest degradation in most participating countries. In addition, we observed that the 15 participant countries received a total of USD 702.36 million for REDD+ readiness preparation. However, most countries have received less than USD 10 million for their readiness-related activities. We observed a huge disparity regarding the funds received between countries from sub-Saharan Africa and their Asian and Latin American counterparts, particularly Indonesia and Peru, respectively. Furthermore, almost all countries have spent their funds on policy and strategy development, stakeholder and consultation events, and public awareness creation. Relatively small amounts have been spent on capacity building and training. Thus, international donors need to focus on strengthening institutional capacities and building effective forest governance structures in countries participating in REDD+, and they should also provide platforms to engage with participant countries to tackle the main deforestation and forest degradation drivers. We suggest further studies to identify high-performing countries that have received lower-than-average funding, consider their deforestation pressures, the size of forests, and the emission reduction potential.